High Iron-Sequestrating Bifidobacteria Inhibit Enteropathogen Growth and Adhesion to Intestinal Epithelial Cells In vitro - Vazquez-Gutierrez, Pamela; de Wouters, Tomas; Werder, Julia; Chassard, Christophe; Lacroix, Christophe (Frontiers in Microbiology, 2016)
The gut microbiota plays an important role in host health, in particular by its barrier effect and competition with exogenous pathogenic bacteria. In the present study, the competition of Bifidobacterium pseudolongum PV8-2 (Bp PV8-2) and Bifidobacterium kashiwanohense PV20-2 (Bk PV20-2), isolated from anemic infant gut microbiota and selected for their high iron sequestration properties was investigated against Salmonella Typhimurium (S. Typhi) and Escherichia coli O157:H45 (EHEC) by using co-culture tests and assays with intestinal cell lines. Single and co-cultures were carried out anaerobically in chemically semi-defined low iron (1.5 µM Fe) medium (CSDLIM) without and with added ferrous iron (30 µM Fe). Surface properties of the tested strains were measured by bacterial adhesion to solvent xylene, chloroform, ethyl acetate, and to extracellular matrix molecules, mucus II, collagen I, fibrinogen, fibronectin. HT29-MTX mucus-secreting intestinal cell cultures were used to study bifidobacteria competition, inhibition and displacement of the enteropatogens. During co-cultures in CSDLIM we observed strain-dependent inhibition of bifidobacterial strains on enteropathogens, independent of pH, organic acid production and supplemented iron. Bp PV8-2 significantly (P<0.05) inhibited S. Typhi N15 and EHEC after 24 h compared to single culture growth. In contrast Bk PV20-2 showed less inhibition on S. Typhi N15 than Bp PV8-2, and no inhibition on EHEC. Affinity for intestinal cell surface glycoproteins was strain-specific, with high affinity of Bp PV8-2 for mucin and Bk PV20-2 for fibronectin. Bk PV20-2 showed high adhesion potential (15.6 +/- 6.0 %) to HT29-MTX cell layer compared to Bp PV8-2 (1.4 +/- 0.4 %). In competition, inhibition and displacement tests, Bp PV8-2 significantly (P<0.05) reduced S. Typhi N15 and EHEC adhesion, while Bk PV20-2 was only active on S. Typhi N15 adhesion. To conclude, bifidobacterial strains selected for their high iron binding properties inhibited S. Typhi N15 and EHEC in co-culture experiments and efficiently competed with the enteropathogens on mucus-producing HT29-MTX cell lines. Further studies in complex gut ecosystems should explore host protection effects of Bp PV8-2 and Bk PV20-2 mediated by nutritional immunity mechanism associated with iron-binding.